Politics of Language in Indonesia (1975-2015): Study of History and Language Policy - Sudaryanto Sudaryanto; Soeparno Soeparno; Lilis Ferawati (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Indonesia has a political concept of language that is always updated in a certain period of time. The concept was born from a scientific meeting entitled “Seminar Politik Bahasa Nasional” (1975), “Seminar Politik Bahasa” (1999) and finally, “Seminar Politik Bahasa” (2015). Each scientific meeting produces a concept of language politics that is complementary and updates the previous concept. Furthermore, the concept of language politics is closely related to the implementation of a language policy in Indonesia. The research method used is content analysis. The data sources used are books, document archives, and photographs that record language political events over a period of 40 years. The results of this study indicate that (1) the concept of national language politics in the version of the Seminar Politik Bahasa Nasional (1975) focuses more on aspects of Indonesian, regional languages, and foreign languages; the political concept of the national language version of the Seminar Politik Bahasa (1999) focuses more on aspects of Indonesian language and literature, regional language and literature, and foreign languages, and the national language politics version of the Seminar Politik Bahasa (2015) emphasizes improving the function of Indonesian language into an international language; and (2) the political concept of national language 1975 and 1999 language politics became the elaboration of Pasal 36 UUD 1945 and the 2015 political concept of language became the elaboration of UU No. 24 Tahun 2009 and PP No. 57 Tahun 2014.